Kepemimpinan Di Era Milenial: Studi Literature - Danang Nugroho; Alan Maulana Amrulloh; Ari Sutrisna; Arif Budiman; Dena Septian; Muhammad Arya Kuncara (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The 21st century is the beginning of the era of globalization, this era is marked by the widespread use of technology to make human life easier. This is supported by the dissemination of information which is quite easy and fast. However, because of its convenience and speed, we are easily influenced by negative things. Therefore, we need leaders who are truly wise in dealing with the process of change that is occurring, so that they can maximize existing technologies to achieve the goals they want to achieve. Those who become leaders are people who are optimistic and full of self-confidence, who have strong moral values, vision and mission, and are able to convey their ideas effectively, and are able to build relationships and encourage others. Because leadership plays an important role in bringing about major changes in an organization, leadership becomes a character that has influence, and leadership is the art of making an organization stable and suitable.